VIII - Síndrome de Bálint relacionada a epilepsia - Kimaid, P. A T [UNESP]; Resende, Luiz Antonio de Lima [UNESP]; Stabenow, P. R.; Montovani, Jair Cortez [UNESP] (My University, 1996)
A review of the literature showed that the Bálint's syndrome is due to bilateral parieto-occipital lesions. In the present report, the authors describe a case of Bálint's syndrome which appeared after several simple partial epileptic seizures related to a right parietal localization. The benign course with full recovery is an example of the fact that the Bálint's syndrome may be related to reversible functional alterations of the cerebral cortex.
Bálint's syndrome related to epilepsy
Keywords: Bálint's syndrome; Epilepsy